Orchid diseases caused by Fusarium oxysporum species complex in Taiwan - Chang, An; Chang, Che-Wei; Wu, Cheng-Chun; Lin, Kuo-Hsi; Chookoh, Nittaya; Unartngam, Jintana; Chung, Wen-Hsin (Frontiers in Plant Science, 2026)
Orchid diseases caused by Fusarium spp. are common in orchid gardens worldwide, with F. oxysporum being the most dominant species. F. oxysporum is defined as a species complex, FOSC. In Taiwan, orchids are highly diverse, and certain species are economically important. However, orchid diseases caused by FOSC remain unclear. In this study, 63 FOSC isolates were collected from commercial orchids, including five epiphytic, one semi-terrestrial, and two terrestrial orchids. Terrestrial orchids were the major hosts of isolated FOSC (41/63). The isolates were confirmed to be pathogenic through mycelium plug or spore suspension inoculation, and they were subsequently used for further analyses. Phylogenetic analyses indicated that FOSC isolates could be separated into six taxa, F. contaminatum, F. cugenangense, F. curvatum, F. nirenbergiae, F. odoratissimum, and F. triseptatum, based on cmdA, rpb2, tef1, and tub2 gene sequences. This classification is also associated with morphological characteristics. These results provide a preliminary insight into pathogenic FOSC in orchids and can be used to explore potential resistant cultivars or screen for effective management agents.